EFFECT OF MASSAGE BEFORE WARM-UP ON THE VERTICAL RELAXATION OF 57 BASKETERS FROM THE ZOU DEPARTMENT IN BENIN - YESSOUFOU, Lafiou; DOSSOU, Sémako Gérard; LAWANI, MOHAMED MANSOUROU; KORA ZAKI, Issifou; TIGRI, Tertutie Nawal; HOUETO, Vignon Gratien; AGASSOUNON, Mahougnon Méschac (My University, 2021)
The use of sports massage as part of passive warm-up is a practice that has been trivialized by many clubs, which consider that massage is only useful in the context of recovery or rehabilitation. The aim of this study is to check if the massage before warming up further increases the vertical relaxation in basketball players from Zou. 57 players were selected including 13 players from Flambeau Abomey; 15 Lumière players from Abomey and 29 players from Olympic of Bohicon using the simple random method by reasoned choice. Our players are aware of the existence of massage but not as passive warm-up. Without warming up or massage our subjects have on average 43.19 cm of relaxation. After the players warmed up without being massaged we observed an increase in relaxation of an average of 48.96cm and 50.61cm when the players massaged and warmed up. The results of our study reveal that massage before heating further increases the vertical relaxation of basketball players from Zou, Benin.
Keywords: Massage; Warm-up; Vertical relaxation; Zou; Benin